Long-term persistence of immunity and B-cell memory following Haemophilus influenzae type B conjugate vaccination in early childhood and response to booster. - Perrett, K; John, T; Jin, C; Kibwana, E; Yu, L; Curtis, N; Pollard, A (2014)
BACKGROUND: Protection against Haemophilus influenzae type b (Hib), a rapidly invading encapsulated bacteria, is dependent on maintenance of an adequate level of serum antibody through early childhood. In many countries, Hib vaccine booster doses have been implemented after infant immunization to sustain immunity. We investigated the long-term persistence of antibody and immunological memory in primary-school children following infant (with or without booster) Hib vaccination. METHODS: Anti-polyribosylribitol phosphate (PRP) immunoglobulin G (IgG) concentration and the frequency of circulating Hib-specific memory B cells were measured before a booster of a Hib-serogroup C meningococcal (MenC) conjugate vaccine and again 1 week, 1 month, and 1 year after the booster in 250 healthy children aged 6-12 years in an open-label phase 4 clinical study. RESULTS: Six to 12 years following infant priming with 3 doses of Hib conjugate vaccine, anti-PRP IgG geometric mean concentrations were 3.11 µg/mL and 0.71 µg/mL and proportions with anti-PRP IgG ≥1.0 µg/mL were 79% and 43% in children who had or had not, respectively, received a fourth Hib conjugate vaccine dose (mean age, 3.9 years). Higher baseline and post-Hib-MenC booster responses (anti-PRP IgG and memory B cells) were found in younger children and in those who had received a fourth Hib dose. CONCLUSIONS: Sustained Hib conjugate vaccine-induced immunity in children is dependent on time since infant priming and receipt of a booster. Understanding the relationship between humoral and cellular immunity following immunization with conjugate vaccines may direct vaccine design and boosting strategies to sustain individual and population immunity against encapsulated bacteria in early childhood. Clinical Trials Registration ISRCTN728588998.